Persuasive Strategic Communication: Tabligh in Komunitas Anak Muda Berhijrah or Hijrah Youth Community - siti sakhinah; Armawati Arbi (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractThe phenomenon of hijrah is becoming a trend among youth today. This study is aims to find out the persuasive communication strategies of Terang Jakarta, an Islamic youth community, to persuade youth to do hijrah through new media (social media), non-media, and their relevance to Islamic persuasive communication. This study uses qualitative research method with a descriptive approach. The results of this study are that three persuasive communication strategies can be applied both in new media and non-media. New media serves as the first gate of Tabligh, where the uses of graphics design and language are the main focus. Afterwards, non-media or face-to-face communication used as a continuation of da’wah through new media, is easier to build emotional relationships and persuasive youth here. Then, the psychodynamic strategy is the most strategies that can be applied both through new media and non-media.AbstrakFenomena hijrah menjadi tren di kalangan anak muda saat ini. Penelitian ini bertujuan mengetahui strategi komunikasi persuasif Terang Jakarta, sebuah komunitas pemuda Islam, untuk mengajak pemuda berhijrah melalui media baru, non media, dan apa relevansinya dengan komunikasi persuasif Islam. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif. Hasil dari penelitian ini adalah tiga strategi komunikasi persuasif dapat diterapkan baik di media baru maupun non media. Media baru (media sosial) merupakan pintu gerbang pertama Tabligh, di mana penggunaan desain grafis dan bahasa menjadi fokus utamanya. Setelah itu, komunikasi non media atau komunikasi tatap muka yang digunakan sebagai kelanjutan dakwah melalui media baru, lebih mudah untuk membangun hubungan emosional dan persuasif remaja di sini. Kemudian, strategi psikodinamik merupakan strategi yang paling banyak diterapkan baik melalui media baru maupun non media.